Single arm meta-analysis of the J-Valve system for aortic regurgitation in Chinese populations - Gao, Lei; Mao, Rui; Zeng, Jie; Wen, Lin (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis meta-analysis aimed to evaluate the efficacy and safety of J-valve in patients with Aortic regurgitation (AR).MethodsPubMed, Embase, the Cochrane Library, and Web of Science databases were searched from inception to November 2024. Primary outcome included Procedural Success, and secondary outcome included In-Hospital Mortality, 30-Day Mortality, One-Year All-Cause Mortality, Stroke Incidence and Complications. The risk of bias was assessed by subgroup analysis, sensitivity analysis, and publication bias, including funnel plot, Egger's test, and Begg's test.ResultsA total of 9 studies involving 552 patients were included in this meta-analysis. The results indicated a surgical success rate of 96% (95% CI: 0.94–0.99). The in-hospital mortality rate was 3% (95% CI: 0.01–0.04), the 30-day mortality rate was 3% (95% CI: 0.01–0.05), and the 1-year all-cause mortality rate was 6% (95% CI: 0.04–0.08). Additionally, the incidence of stroke was 2% (95% CI: 0.01–0.03), and the incidence of other complications was 22% (95% CI: 0.16–0.28).ConclusionsThis meta-analysis indicates that the J-Valve prosthesis exhibits favorable short-term efficacy in patients with severe aortic regurgitation (AR); however, a significant incidence of complications persists. A thorough risk assessment is crucial when determining the appropriate treatment strategy. Furthermore, postoperative follow-up duration should be extended to monitor patient outcomes effectively.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024552406, identifier CRD42024552406.